A Special Chinese Reading Acceleration Training Paradigm: To Enhance the Reading Fluency and Comprehension of Chinese Children with Reading Disabilities - Dai, Li; Zhang, Chenchen; Liu, Xiangping (Frontiers in Psychology, 2016)
According to a number of studies, use of a Reading Acceleration Program as reading intervention training has been demonstrated to improve reading speed and comprehension level effectively in most languages and countries. The objective of the current study was to provide further evidence of the effectiveness of a Reading Acceleration Program for Chinese children with reading disabilities using a distinctive Chinese reading acceleration training paradigm. The reading acceleration training paradigm is divided into a non-accelerated reading paradigm, a Character-accelerated reading paradigm and a Words-accelerated reading paradigm. The results of training Chinese children with reading disabilities indicate that the acceleration reading paradigm applies to children with Chinese-reading disabilities. In addition, compared with other reading acceleration paradigms, Words- accelerated reading training is more effective in helping children with reading disabilities read at a high speed while maintaining superior comprehension levels.